Integrating Disturbance Handling into Control Strategies for Swing-up And Stabilization of Rotary Inverted Pendulum - Nguyen, Thi-Van-Anh; Phan, Ma-Sieu; Dao, Quy-Thinh (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
The rotary inverted pendulum (RIP) is an underactuated mechanical system with fewer input controls than output controls. The application of the RIP model is to investigate the control of nonlinear systems and in other fields as well, as it is simple to analyze the dynamics and test despite its high nonlinearity. The two fundamental control issues in the RIP are achieving the desired balance position of the pendulum and maintaining stability. The energy-based swing-up controller is used for the model to bring the pendulum to an upright position. Regarding the issue of stability control, the LQR linear controller is well-known for its effectiveness and good stability, but it lacks stability in the presence of disturbance. The sliding mode controller (SMC) is able to resist the impact of disturbances when they affect the model. Therefore, this paper combines both controllers to address the balancing stability problem of the RIP system. The LQR-based SMC controller uses the LQR controller as the basic controller to stabilize the pendulum and employs the SMC controller to resist the impact of disturbance. In addition, it is necessary to accurately estimate the velocity of the pendulum and arm in order to apply them to the real model. This paper designs an observer to solve this problem. The simulation results show that the proposed controller performs well in the presence of input disturbance.